Geographic variation in flower color: spectral composition versus perception of pollinators - Baranzelli, M. (2013)
Fil: Baranzelli, M. Universidad Nacional de Córdoba. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Multidisciplinario de Biología Vegetal; Argentina.